STUDY OF IRON CHELATING AND DNA PROTECTIVE ACTIVITIES IN HYDROALCOHOLIC EXTRACT OF INDIAN MEDICINAL PLANTS - R. SARKAR; N. MANDAL (International Journal of Pharma and Bio Sciences, 2012)
The study evaluated the in vitro iron chelating, lipid peroxidation inhibitory and DNA protective activities of hydroalcoholic (60% ethanolic) extracts of various plant parts of Terminalia chebula, Caesalpinia crista, Cajanus cajan, Terminalia belerica, Emblica officinalis, and Tinospora cordifolia. The iron chelating property of the plants is in accordance with the order of their IC50 values following the trend T. chebula > T. belerica > E. officinalis > C. cajan > T. cordifolia > C. crista. The inhibitory activity of lipid peroxidation of the plant extracts followed the order T. belerica > E. officinalis > T. chebula > C. cajan > T. cordifolia > C. crista. All the plants showed reasonable DNA protective ability in the order T. chebula > E. officinalis > T. belerica > C. crista > C. cajan > T. cordifolia. These results furthermore strengthen the antioxidant potential of the plants, through their iron chelating abilities.